Design, synthesis and evaluation of VEGF-siRNA/CRS as a novel vector for gene delivery - Zhao W; Zhang YF; Jiang XY; Cui CY (Dove Medical Press, 2016)
Wen Zhao, Yifan Zhang, Xueyun Jiang, Chunying Cui School of Chemical Biology and Pharmaceutical Sciences, Capital Medical University, Beijing, China Abstract: Small interfering RNA (siRNA) delivery is a prospective method in gene therapy, but it has application limitations such as negative charge, water solubility and high molecular weight. In this study, a safe and efficient nano-vector, CRS, was designed and synthesized to facilitate siRNA delivery. Physical and chemical properties of VEGF-siRNA/CRS were characterized by methods including scanning electron microscopy (SEM), transmission electron microscopy, zeta potential (ζ) measurement, drug-releasing rate measurement, gel electrophoresis and confocal microscopy. The biological activities were evaluated using cell viability assay, gene-silencing efficacy assay in vitro, real-time polymerase chain reaction, enzyme-linked immunosorbent assay (ELISA) and antitumor tests in vivo. The mean nanoparticle size of VEGF-siRNA/CRS was 121.4±0.3 nm with positive ζ potential of 7.69±4.47 mV. The release rate of VEGF-siRNA from VEGF-siRNA/CRS was 82.50% sustained for 48 h in Tris-ethylenediaminetetraacetic acid buffer (pH 8.0). Real-time polymerase chain reaction was used to analyze the efficiency of the transfection, and the result showed that VEGF mRNA expression had been knocked down by 82.36%. The expression of VEGF protein was also recorded to be downregulated to 14.83% using ELISA. The results of cytotoxicity measured by Cell Counting Kit-8 assay showed that VEGF-siRNA/CRS had significant inhibitory effect on HeLa cells. The results of antitumor assays indicated that VEGF-siRNA/CRS exhibited tumor cell growth inhibition in vivo. The results demonstrated that VEGF-siRNA could be delivered and transported by the designed carrier, while siRNA could be released constantly and led to an increasing gene-silencing effect against VEGF gene. In conclusion, VEGF-siRNA/CRS is a promising carrier for siRNA delivery, and further studies are warranted. Keywords: CRS, siRNA delivery, VEGF, tumor therapy, antitumor, biophysical characteristics, gene silencing, protein expression